2016
DOI: 10.1038/srep38125
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Tunneling-Magnetoresistance Ratio on Nanoscale Spacer Thickness and Material for Double MgO Based Perpendicular-Magnetic-Tunneling-Junction

Abstract: It was found that in double MgO based perpendicular magnetic tunneling junction spin-valves ex-situ annealed at 400 °C, the tunneling magnetoresistance ratio was extremely sensitive to the material and thickness of the nanoscale spacer: it peaked at a specific thickness (0.40~0.53 nm), and the TMR ratio for W spacers (~134%) was higher than that for Ta spacers (~98%). This dependency on the spacer material and thickness was associated with the (100) body-centered-cubic crystallinity of the MgO layers: the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…To address those concerns, W was recently reported to replace Ta as spacer and bridging layers in top-pinned p-MTJ films. [32][33][34][35][36][37] A TMR of 141% after 400 °C annealing 2 and a Δ of 61 have been obtained from blank films. 34 These improvements were partially attributed to the suppression of atom diffusion and crystalline structure of the W layer, whereas the essential role of W layers in TMR enhancement has not been clearly revealed.…”
mentioning
confidence: 99%
“…To address those concerns, W was recently reported to replace Ta as spacer and bridging layers in top-pinned p-MTJ films. [32][33][34][35][36][37] A TMR of 141% after 400 °C annealing 2 and a Δ of 61 have been obtained from blank films. 34 These improvements were partially attributed to the suppression of atom diffusion and crystalline structure of the W layer, whereas the essential role of W layers in TMR enhancement has not been clearly revealed.…”
mentioning
confidence: 99%
“…For example, the previous bottom CoFeB free layer has been changed to a top CoFeB free layer for increasing the TMR ratio 14 and the single MgO-based p-MTJ spin-valve design has been changed to a double MgO-based p-MTJ spin-valve design for enhancing thermal stability 15 17 . In addition, it has been shown that a p-MTJ spin-valve incorporating a tungsten (W) based seed, bridging, and capping layer, instead of the tantalum (Ta) used in our previous study, enhances both the TMR ratio and thermal stability 14 , 18 , 19 . However, a double MgO-based p-MTJ spin-valve structure with a top CoFeB free layer remains a challenging target, because the roughness of the MgO tunneling barrier lower the TMR ratio 20 – 24 .…”
Section: Introductionmentioning
confidence: 88%
“…In the double CoFeB-MgO interface structure, a thin metal layer such as Ta, W, or Mo was inserted to absorb boron from the CoFeB layers (MgO/CoFeB/insertion layer/CoFeB/MgO) for high tunnel magnetoresistance (TMR) ratio and perpendicular anisotropy [15,16,29,[33][34][35][36][37][38][39][40][41][42][43][44]. First, Ta was used as insertion material because Ta has a bcc crystal structure and is a good boron absorber, as mentioned above.…”
Section: (1) High Thermal Tolerance By Controlling Boron Composition mentioning
confidence: 99%
“…First, Ta was used as insertion material because Ta has a bcc crystal structure and is a good boron absorber, as mentioned above. Recently, tungsten (W) was also used as insertion material because W has a higher melting point, resulting in higher thermal stability [39,44].…”
Section: (1) High Thermal Tolerance By Controlling Boron Composition mentioning
confidence: 99%